Legal Protection for Land Rights Owners in the Name Change Process Following the Burning Down of the Brebes District Land Office - Wulandari, Wina (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The fire incident resulted in the destruction of land documents. As happened at the Brebes BPN Office, the fire disaster caused damage to the 2023 Complete Systematic Land Registration (PTSL) certificate which was ready to be submitted, approximately 6000 files were being worked on. The impact of the fire at the Brebes BPN Office will cause land services to be hampered and the escalation of land conflict disputes to increase. The purpose of this study was to determine the legal protection for land rights owners in the name change process after the Brebes Regency Land Office burned down and the efforts of the land office for land rights owners. This research is an empirical research. In terms of the type of data, the research approach used in this study is a qualitative approach. This study uses primary data types and sources supported by secondary data. The data analysis technique used in this study is a qualitative descriptive method. The results of the study stated that legal protection for landowners after the Brebes Land Office fire involved the restoration of certificates and land books by the BPN based on Perkaban Number 6 of 2010. The name change process can be assisted by a legal expert or notary, with the landowner including important documents and coordinating with related parties. The Brebes Land Office carried out land certificate data recovery after the fire, although the negative land registration system has weaknesses. Recovery follows the Head of Agency Regulation Number 6 of 2010 concerning disaster management and the return of community rights to land assets in disaster areas.Keywords: Land; Protection; Rights.